A revision of the genus Paraleptognathia Kudinova-Pasternak, 1981 (Crustacea: Tanaidacea) and description of four new species - Guerrero-Kommritz, Jürgen (Zootaxa, 2004)
The genus Paraleptognathia, a common representative of the deep-sea and polar faunas, has been revised. The genus Akanthophoreus Sieg, 1986 has been synonymized with Paraleptognathia. A new definition and description of the genus Paraleptognathia, redescriptions of nine species [P. alba (Hansen, 1913), P. antarctica (Vanh ffen, 1914), P. australis (Beddard, 1886), P. brachiata (Hansen, 1913), P. gracilis (Kr yer, 1842), P. inermis (Hansen, 1913), P. longiremis (Lilljeborg, 1864), P. multiserrata (Hansen, 1913), P. weddellensis (Sieg, 1986)], and descriptions of four new species (P. multiserratoides n. sp., P. benguela n. sp., P. fastuosa n. sp., P. tenuichela n. sp.) are presented. The 16 species of Paraleptognathia are discussed.